Production du sol urbain et vulnérabilité aux inondations : l’exemple de la cité Sidi Hcine Essijoumi en Tunisie - Najem Dhaher (Confins, 2011)
The growth of the cities in the countries of the south demonstrates the weight of settlement and access to urban land through speculation mechanisms associated to some particularities of the urban land market. The major problem of those cities is the incoherence between planning, setting up of public utilities and the actual development of the occupation. This situation has often generated a development of the illegal city. These problems and dysfunctions, which affect everyday life of the cities, are the result in the way the building space, the functions, the utilities and populations are set up and of dysfunctions generated by the absence of rational politics concerning land ownership. This type of city development also causes growth of impermeabilised surfaces that generate an increase in the risks of flooding. But the causes of flooding are not limited to these.